Organisasi Pendidikan dalam Perspektif Islam - Hairul Puadi (JURNAL PUSAKA: Media Kajian dan Pemikiran Islam, 2025)
A simple definition of “organization” that can be applied is: “An organization is a system of reciprocal influence among people in a group who work together to achieve certain goals.” The implementation of the organization will be concrete if there are aspects that are quite important for the organizational process, namely: (1) Organizational identity. (2) Organizational principles. (3) Formulation of goals. (4) Organizational culture. (5) Management levels. Identity is not just a name, but an organizational structure must be formed so that its management is clear. The principles of the organization have two roles, namely: (1) As a guideline in a healthy and efficient organization. (2) As a foundation in carrying out organizational activities. Meanwhile, the formulation of objectives can be explained as follows: (1) Specific. (2) Time-limited. (3) Measurable. (4) Challenging. (5) Achievable. In an organization there are also dynamics of the relationship between individual goals and organizational goals, namely: (1) Totally contradictory. (2) Partially contradictory. (3) Neutral. (4) Appropriate. (5) Exactly the same. In the context of organizational development, several functions of organizational culture: (1) Culture as a differentiator between one organization and another. (2) Culture as a shaper of organizational identity. (3) Culture as an organizational glue. (4) Culture as a control tool. In an organization there are three levels of management: (1) Top Management. (2) Middle Management. (3) First Line Management.